2018
DOI: 10.1007/s10616-018-0228-2
|View full text |Cite
|
Sign up to set email alerts
|

Neutralizing FGF4 protein in conditioned medium of IL-21-silenced HCT116 cells restores the migratory activity of the colorectal cancer cells

Abstract: The interleukin-21 (IL-21) protein was found to be expressed at an elevated level in clinical samples of colorectal cancer patients without or with a parasitic infection that were collected from Sudan in our previous study. The IL-21 gene in HT29 and HCT116 cells was then correlated to cell proliferation and cell migration, as well as the cellular mechanisms associated with gene expressions in our present study. Our results demonstrated that silencing the IL-21 gene in HCT116 cells increased the cytotoxic leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…3B ). As the cells transfected with scrambled siRNA did not exhibit any significant differences compared with non-transfected cells in our previous study ( 7 , 10 ), non-transfected cells were used as control. Evaluation of the mRNA expression level of the cell proliferation markers Ki67 and PCNA using RT-qPCR demonstrated that the mRNA expression levels of Ki67 and PCNA were decreased in the IL-21-silenced HCT116 cells compared with those in the controls.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…3B ). As the cells transfected with scrambled siRNA did not exhibit any significant differences compared with non-transfected cells in our previous study ( 7 , 10 ), non-transfected cells were used as control. Evaluation of the mRNA expression level of the cell proliferation markers Ki67 and PCNA using RT-qPCR demonstrated that the mRNA expression levels of Ki67 and PCNA were decreased in the IL-21-silenced HCT116 cells compared with those in the controls.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon may also explain the relationship between parasitic infection and colorectal cancer. IL-21 was the focus of the present study, as a high level of IL-21 expression has been detected in colorectal cancer cells, such as HT29 and HCT116( 7 ). In our previous study, a high level of IL-21 was also detected in the serum samples of patients diagnosed with colorectal cancer with a history of parasitic infections ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fibroblast growth factor 4 [FGF4] is a member of the FGF superfamily, which is involved in numerous stages of embryonic development and enhances multiple oncogenic activities, including tumor proliferation, invasion/migration, and colony initiation abilities [63,64]. Although there are some reports on the involvement of FGF4 in the processes of cancers, including lung adenocarcinoma, colorectal cancer, breast cancer, and ovarian cancer [65][66][67][68], little is known about the involvement of FGF4 in HCC. In this study, we found, for the first time, that FGF4 was highly expressed in HCC, suggesting a role as a novel serum biomarker for HCC.…”
Section: Discussionmentioning
confidence: 99%